Open access to science education resources and learning designs in Europe - Sampson, Demetrios; Zervas, P.; Sotiriou, S. (2012)
Over the past years a large amount of digital science education resources became available for open access through web-based repositories. These resources have the potential to support technology-enhanced science education by enabling science teachers to improve their day-to-day science teaching. Nevertheless, it has been identified that science teachers could benefit from their participation in communities of best science teaching practices by sharing, not only digital educational resources, but also learning designs that represent their pedagogical practice. This hasled to efforts on moving beyond web-based repositories of digital educational resources towards the development of web-based repositories of learning designs. Within this framework, the aim of this paper is to provide an overview of three (3) European initiatives, which aim to support and facilitate open access to Educational Resources and Learning Designs in the field of Science Education, namely, the Open Science Resources Repository, the COSMOS Repository and the PATHWAY Coordination and Support Action. © 2012 IEEE.